Asuhan Keperawatan Keluarga Pada Keluarga Dengan Stunting di Wilayah Kerja Puskesmas Padusunan Kota Pariaman - tassya juahari; Armaita; Hasmita; Sandra Dewi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
According to data from the World Health Organization (WHO) in 2023, an estimated 141.8 million (22.3%) children under five worldwide were affected by stunting. Indonesia ranks as the third country with the highest prevalence of stunting in Southeast Asia, with a prevalence rate of 36.4%. The purpose of this study was to provide family nursing care for a patient with stunting in the working area of Padusunan Community Health Center. Stunting is a health problem characterized by impaired physical growth in children due to chronic malnutrition, particularly during the first 1,000 days of life, from pregnancy until the child reaches two years of age. The method used was the nursing process, consisting of assessment, nursing diagnosis, nursing intervention, implementation, and evaluation. The research design employed was descriptive with a case study approach. The results of the study conducted from March 5, 2026, to March 10, 2026, identified three nursing diagnoses: Nutritional Deficit in Child A related to the family's inability to recognize health problems, as evidenced by Mrs. N's statement that the child’s weight was difficult to increase and that the child had a poor appetite; Knowledge Deficit related to inadequate exposure to information, as evidenced by Mrs. N's statement that she lacked creativity in preparing meal menus for her child; and Ineffective Health Maintenance related to the inability to care for a sick family member. The implementation results showed an improvement in family knowledge regarding stunting and increased involvement in patient care. The interventions provided included nutrition management, health education, and education on health-promoting behaviors. It can be concluded that comprehensive family nursing care is able to improve family independence in caring for family members with stunting. The completion of nursing care is expected to increase knowledge and awareness regarding the fulfillment of balanced nutritional needs.